Prognosis of progression of chronic generalised periodontitis in patients with bronchiectatic disease - Artem K. Sarkisov; Vladimir A. Zelenskiy; Ekaterina A. Polunina; Karen A. Sarkisov (Кубанский научный медицинский вестник)
Aim. To analyse the parameters of dental indices and the level of markers of infl ammation and oxidative stress in patients with chronic generalised periodontitis (CGP) with bronchiectatic disease and to develop a mathematical model for assessing the risk of CGP progression in patients with bronchiectatic disease.Materials and methods. A total of 70 patients with mild and moderate CGP were examined, which were divided into the following groups: patients with CGP without general somatic pathology (n = 33), and patients with CGP and bronchiectatic disease (n = 37). The control group consisted of somatically healthy individuals with intact periodontium (n = 40). Dental indices (PMA, PI, Muhlemann, OHI-s), infl ammatory markers (transforming growth factor beta 1 (TGFβ-1), lactoferrin (LF), interleukin-8 (IL-8), C — reactive protein (CRP)), and oxidative stress markers (malondialdehyde (MDA), as well as advanced oxidation protein products (AOPPs), and total superoxide dismutase (SOD)) were analysed in all patients included in the study. The method of binary logical regression was used to create a mathematical model for assessing the risk of CGP progression in patients with bronchiectatic disease.Results. Dental indices and the level of markers of infl ammation and oxidative stress were statistically signifi cantly higher in all patients with CGP as compared to somatically healthy individuals, as well as in patients with CGP and bronchiectatic disease as compared to patients with CGP without general somatic pathology. Positive correlations of different strength between the studied markers of infl ammation and oxidative stress and dental indices were revealed. Based on the results of the correlation matrix data and using the binary logistic regression method, a mathematical model was developed that can be applied for assessing the risk of CGP progression in patients with bronchiectatic disease. The predictors of progression included in the mathematical model were: PI, TGFβ-1 and AOPPs. Conclusion. The data obtained indicate a greater severity of infl ammation and oxidative stress in CGP patients with comorbid pathology in the form of bronchiectatic disease and the infl uence of these processes on the periodontal condition. The proposed mathematical model for assessing the risk of CGP progression in patients with bronchiectatic disease is characterized by a high level of sensitivity and prognostic signifi cance, thus being applicable for use in clinical practice.